HORMONE REPLACEMENT THERAPY PERIMENOPAUSE. AN ALTERNATIVE FOR WOMEN WHO DO NOT WANT MENSTRUATING. PRELIMINARY STUDY - Siu, Alejandro (2015)
OBJETIVE: To evaluate the results of the administration of tibolone for HRT in perimenopausal uterine bleeding still present. Design: Clinical observational study. MATERIALS AND METHODS: Fifty perimenopausal women with higher serum FSH 40 IU / mL and absence of gynecological pathology, who combined treatment of tibolone and birth control pills administered in order to bring down the endometrium, then prescribe tibolone alone. RESULTS: 50% of the studied patients responded successfully to this therapeutic regimen. CONCLUSION: The therapy combined tibolone and birth control pills can be achieved amenorrhea in a group of perimenopausal women.